Prodromal symptoms of out-of-hospital cardiac arrest among patients calling emergency and non-emergency medical help services. (14th October 2021) - Zylyftari, N; Lee, C.J.-Y; Gnesin, F; Moeller, A.L; Mills, E.H.A; Moeller, S.G; Jensen, B; Ringgren, K.B; Christensen, H.C; Blomberg, N.F; Tan, H.L; Folke, F; et al.
Abstract: Background: Early identification of individuals at risk of out-of-hospital cardiac arrest (OHCA) remains difficult. Little is known about symptoms presented when contacting a medical helpline prior to OHCA. Aim: To examine the registered prodromal symptoms when patients phoned to seek medical help prior to OHCA. Methods: OHCA patients (≥18 years) were identified from the Danish Cardiac Arrest Registry (2014–2018) and linked with calls to the non-emergency (1813-Medical Helpline) and Emergency Medical Services 1–1-2 (112). We examined (1) symptoms registered within 30 days before OHCA, categorized into eight groups and stratified by time-period and call-type; (2) hospital diagnoses and medical prescriptions according to symptom groups within 180 days before these calls. Results: Among 974 OHCA patients who called in total within 30 days before OHCA, 816 OHCA patients (males 57%, median age 76 years [Q1-Q3: 65–84]) had a registered symptom and some of them called more than once (1, 145 calls by 816 patients). Overall, the most reported group of symptoms was "Other" (29%), containing a diverse group of prodromal symptoms registered by the caregiver that did not fit into the other categories (Figure), followed by breathing problems (15%). When stratified by time-period (Figure) the most common symptom group remained "Other". This was followed by symptoms related to the Central Nervous System (CNS)/Unconsciousness (17%) for the time-period within 0–7 days before OHCA, and by breathing problems (19%) and trauma/exposure (17%) for the time-period within 8–30 days before OHCA (Figure). When stratified by call-type, most patients (60.8%) called the 1813-Medical Helpline, where "Other" (35%) and abdominal/back/urinary (14%) symptom groups were the most common. While breathing problems (24%) and CNS/Unconsciousness (21%) were highly reported among calls to 112. Within 180-days before contact with the medical helpline, independently of the symptom group presented, respiratory-related hospital diagnoses and antibiotic medications were common. Conclusions: Patients with OHCA who called emergency and non-emergency medical helpline 30 days before OHCA had diverse prodromal symptoms; the largest category were "Other" symptoms, followed by breathing-related symptoms. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 under the ESCAPE-NET program;Helsefonden